Mechanisms of phase transformations in iron - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2022)
Gibbs molar volumetric energy and iron boundary molar energy are determined depending on temperature. It has been shown that phase transformations in iron occur under thermodynamically equilibrium conditions. The iron phase microcrystals are dendrites. Crystallization of the iron melt is a nanostructural process. Iron recrystallization has been shown to be a largely diffuse process.